Corrosion Inhibition Effect of the Essential Oil of Dried and Fresh Crystal Seedless Guava Leaves (Psidium guajava) in Acid Medium - Lilik Suprianti; Nove Kartika Erliyanti; Caecilia Pujiastuti (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
This research studied the corrosion inhibition activities of the essential oil of crystal seedless guava leaves (Psidium guajava) in an acid medium. The essential oil (EO) was extracted from the different treatments of raw materials (fresh and dried leaves) using the microwave hydrodistillation method with a power of 600 Watt. Water was used as the solvent, with the ratio of feed to solvent (w/v) 1:7. The extraction duration was over 3 hours. The extraction process was done at atmospheric pressure and 100oC. Different raw material treatments result in different yields, where the highest yield was obtained from the dried leave, with the value reaching 1.08%. The essential oil chemical compound was determined by GC-MS analysis. The main component obtained were caryophyllene (44.98%) and Caryophyllene oxide (14.96%). The essential oil was applied as a corrosion inhibitor for carbon steel in a 1 M Hydrochloric acid (HCl) medium. The inhibition efficiency (IE) was 67% at a concentration of 0.3g/L, while the fresh leaves essential oil was only 63%. The dried leave EO performs a higher anti-corrosion effect than the fresh leaves EO. These results show crystal seedless guava leaves' essential oil has anti-corrosion activities on carbon steel in an acid medium.